Electromagnetic pollution in the computer labs: The effects on the learning environment - (:unkn) unknown (My University, 2008)
Electromagnetic fields (EMF) became increasingly a common constituent of the general and workplace environments early in the 20th century. The biological and physiological effects of EMF become a topic of considerable scientific researches during the past two decades. Also, some of scientists claim that EMF causes physiological stress, producing symptoms of tiredness and difficulty concentration. These symptoms could be able to affect the learning environment in negative way. Considering all these points, the purpose of this study is to investigate the effects of EMF on the learning environment of the computer laboratories. The EMF measurements were carried out in four different computer laboratories at Marmara University. To determine the magnitude of EMF in the computer laboratories, the exposure level tester ELT-400 was used. At the end, it was found that the EMF levels around the UPS devices displayed dangerous levels to health, and these results were above the exposure limits set by International Commission on Non-Ionizing Radiation Protection (ICNIRP).